Ensino de relações espaciais de direita e esquerda para indivíduos com autismo e deficiência intelectual - Silva, Elaine de Carvalho (Universidade Federal de São Carlos, 2016)
Children with Autism Spectrum Disorder (ASD) and intellectual disability may experience delays in psychomotor development and flaws in the structuring of the body schema, which subsidize the development of spatial orientation. These delays cause perceptual, motor, and social problems. In the approach of Applied Behavior Analysis (ABA), the behavioral intervention programs use a variety of working formats to meet individual needs of this population. Considering the body notion as a basis for the development of learning, the aim of this study was to teach individuals with ASD and intellectual disability to discriminate sides "right" and "left" of the body and check the generalization of this concept to other stimuli and contexts. Two experiments were carried out. In the first experiment, participants were a boy (9 years old) diagnosed with autism and two teenagers (16 years old), one with Down syndrome and another with intellectual disabilities. In the second experiment, participants were four boys diagnosed with ASD at the age of ten to twelve years. The selection criterion was that the participants did not present the knowledge of concepts related to the left and right sides, identified in a pretest. The procedure consisted of pre-testing, teaching with multiple exemplar instruction and post-test. The intervention was composed of discrete trials in which an instruction containing three components (movement, body part, and laterality, for example, "Raise your right arm") was presented and, when necessary, imitation, physical, and gestural prompts were used and faded according to the participant's performance. Data collection was filmed for reliability calculations and the designs were pre- and post-test in the first experiment and multiple baseline across participants in the second experiment. All participants presented correct responses regarding taught actions involving three components (movement, body part, and laterality), and generalized right and left concepts to new contexts that were tested with the use of objects. This study used only listener verbal relations, opening possibilities for comparing listener relations training and speaker relations training in the emergence of such concepts.
Keywords: Educação especial; Análise do comportamento; Psicomotricidade; Relações Espaciais; Transtorno do espectro do autismo; Deficiência Intelectual; Special education; Applied behavior analysis; Psychomotricity; Spatial relations; Autism spectrum disorders; Intellectual disability; CIENCIAS DA SAUDE::EDUCACAO FISICA; CIENCIAS HUMANAS::PSICOLOGIA; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO ENSINO E DA APRENDIZAGEM